2010
DOI: 10.1007/s10593-010-0498-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the first representative of the 2,3,6,7-tetrahydro-1H-benzo[d]azonine system from 1-cyanomethyl-2-methyl-1,2,3,4-tetrahydroiso-quinolinium chloride and dimethyl acetylene-dicarboxylate

Abstract: In previous work, we were the first to establish the feasibility of a one-step synthesis of the 1,2,3,6-tetrahydroindeno[2,1-c]azonine [1] and 1,2,3,4,7,12-hexahydroazonino[4,5-b]indole heterocyclic systems [2], which had previously been difficult to obtain, in the reaction of quaternary 2,3-dihydro-1H-indeno-[2,1-c]pyridinium or 1,2,3,4-tetrahydro--carbolinium salts with dimethyl acetylenedicarboxylate (2) in the presence of base. Gimranova [3] has also undertaken an attempt to convert a series of N-(ethoxyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…[64] Starting from similar tetrahydroiso- quinolinium salts 121 in combination with dimethyl acetylenedicarboxylate, the same authors achieved a ring enlargement by three carbon atoms under formation of 2,3,6,7-tetrahydro-1H-benz[d]azonines 124 (Scheme 25). [65] More recently, Lahm et al reported a concise synthesis of polycyclic alkaloids based on the Stevens rearrangement of nitrile-stabilized ammonium ylides derived from spirocyclic ammonium salts. Starting from simple cyclic a-aminonitriles 125, the salts 127 were prepared by double N-alkylation with readily available dibromide 126 (two steps from veratrol and diacetyl).…”
Section: Rearrangement Of Nitrile-stabilized Ammonium Ylidesmentioning
confidence: 99%
See 1 more Smart Citation
“…[64] Starting from similar tetrahydroiso- quinolinium salts 121 in combination with dimethyl acetylenedicarboxylate, the same authors achieved a ring enlargement by three carbon atoms under formation of 2,3,6,7-tetrahydro-1H-benz[d]azonines 124 (Scheme 25). [65] More recently, Lahm et al reported a concise synthesis of polycyclic alkaloids based on the Stevens rearrangement of nitrile-stabilized ammonium ylides derived from spirocyclic ammonium salts. Starting from simple cyclic a-aminonitriles 125, the salts 127 were prepared by double N-alkylation with readily available dibromide 126 (two steps from veratrol and diacetyl).…”
Section: Rearrangement Of Nitrile-stabilized Ammonium Ylidesmentioning
confidence: 99%
“…Soldatova and co‐workers employed the same sequence for the ring homologation of tetrahydroisoquinolinium salts to tetrahydro‐3‐benzazepines 64. Starting from similar tetrahydroisoquinolinium salts 121 in combination with dimethyl acetylenedicarboxylate, the same authors achieved a ring enlargement by three carbon atoms under formation of 2,3,6,7‐tetrahydro‐1 H ‐benz[ d ]azonines 124 (Scheme ) 65…”
Section: Rearrangement Of Nitrile‐stabilized Ammonium Ylidesmentioning
confidence: 99%